2022
DOI: 10.1155/2022/1460326
|View full text |Cite
|
Sign up to set email alerts
|

Structural Covariance of the Ipsilesional Primary Motor Cortex in Subcortical Stroke Patients with Motor Deficits

Abstract: The analysis of structural covariance has emerged as a powerful tool to explore the morphometric correlations among broadly distributed brain regions. However, little is known about the interactions between the damaged primary motor cortex (M1) and other brain regions in stroke patients with motor deficits. This study is aimed at investigating the structural covariance pattern of the ipsilesional M1 in chronic subcortical stroke patients with motor deficits. High-resolution T1-weighted brain images were acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This assumes that functionally or structurally connected brain regions also covary in their morphology and that environmental factors influence their coordinated development and thus covariance (for a review, see Alexander‐Bloch & Giedd, 2013). For example, in patients with stroke, alterations in structural covariance were found in a network including the cortico‐striato‐thalamical loop and diverse sensorimotor cortices (Abela et al, 2015) and between the ipsilesional M1 and motor as well as non‐motor brain regions (Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This assumes that functionally or structurally connected brain regions also covary in their morphology and that environmental factors influence their coordinated development and thus covariance (for a review, see Alexander‐Bloch & Giedd, 2013). For example, in patients with stroke, alterations in structural covariance were found in a network including the cortico‐striato‐thalamical loop and diverse sensorimotor cortices (Abela et al, 2015) and between the ipsilesional M1 and motor as well as non‐motor brain regions (Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers come to realize that morphologic alterations of brain regions beyond the lesion are also crucial for clinical recovery (Al Harrach et al, 2019; Merino‐Serrais et al, 2022). For instance, a decrease in grey matter volume (GMV) in motor‐related regions typically indicates poor motor performance after stroke (Chen et al, 2022; Keller et al, 2020). Several studies have associated thickening of contralesional cortex beyond primary motor and sensory areas with the ability of life independence and sensorimotor recovery after stroke (Liu et al, 2015; Rojas Albert et al, 2022), while some studies found no clinical associations of contralesional cortical thickness (CT) (Cheng et al, 2020; Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Motor and cognitive impairments are prevalent after stroke (Zhao et al, 2018;Shekhar et al, 2021;Chen et al, 2022), even in patients with mild strokes (Einstad et al, 2021). Compared to motor function injuries, cognitive function injuries have the characteristics of being concealed and delayed, resulting in patients with cognitive impairment not seeking medical treatment promptly.…”
Section: Introductionmentioning
confidence: 99%